56 ATTENUATION OF RODENT LUNG ISCHEMIA/REPERFUSION INJURY BY SPHINGOSINE 1-PHOSPHATE. (1st March 2005) - Moreno-Vinasco, L.; Bonde, P.; Jacobson, J.; Garcia, J. G.N.
Abstract : Ischemia/reperfusion (I/R) injury is a common sequelae of lung transplantation occurring in donor lungs within hours and associated with significant morbidity and mortality. I/R injury is characterized by alveolar damage, edema, and inflammation. Despite improvements in lung preservation techniques, I/R injury remains a significant cause of lung transplant failure and novel therapeutic interventions are desperately needed. We employed a rodent model to investigate a potential therapeutic role of sphingosine 1-phosphate (S1P), a potent vascular barrier protective product of platelets, in I/R lung injury. Sprague Dawley rats were subjected to thoracotomy and pulmonary artery ligation (1 hr) followed by a period of reperfusion (2 hr). S1P (1 μm final, i.v) was administered either 15 min prior to ischemia or at the time of reperfusion. Indices of lung vascular permeability and inflammation were assessed including bronchoalveolar lavage (BAL) cell counts, differentials and albumin concentrations. Myeloperoxidase activity (MPO) was measured in left lung homogenates as a reflection of parenchymal leukocyte infiltration. BAL fluid from I/R animals pre-treated with S1P contained decreased total number of cells (32.4% decrease, p = 0.05), neutrophils (63.3% decrease p = 0.04) and albumin concentration (57.2% decrease p = 0.04) compared to controls. In addition, S1P administered prior to ischemia resulted in decreased (63.0% decrease p = 0.04) lung tissue MPO. Our findings suggest that S1P significantly attenuates vascular permeability and inflammation associated with I/R injury. Ultimately, our results may have profound clinical implications as S1P may serve as a useful adjunct to current preservation approaches employed during lung transplantation allowing for improved patient outcomes. Funded by HL 073994